The Relationship Between Body Mass Index of Acting 1st Semester Stkip Mbb with Overweight - Khizqil Baharudin Akbar; Yoga Saputra; Windra Windra; Hengki Hartatadi (Universitas Negeri Medan, 2020)
The results of this study indicate that there is a relationship between body mass index and body weight. The relationship between habits or lifestyle with weight is very influential. This happens because the average research subject does not regulate a healthy lifestyle. In this study, 54 students were selected as research subjects consisting of 42 male subjects and 12 female subjects. Most of the subjects in this study had nutritional status that showed a body mass index in the normal weight category of 25 people, overweight subjects as much as 8 people, underweight subjects as many as 6 people, and obese weight subjects as many as 6 people.